PREDIKSI DEBIT HARIAN PADA DAS TIDAK TERUKUR DENGAN MENGGUNAKAN REGIONAL FLOW DURATION CURVE - Elma Yulius (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2014)
Planning projects in the field of water resources engineering usually to be sought dependable flow. Dependable flow of which used as discharge planning is expected to be available in the river to estimate the installed capacity of hydroelectric power, regulate the distribution of drinking water, and estimate the irrigation area. Dependable discharge can be searched by making the Flow Duration Curve for discharge equaled or exceeded. Problems arise when discharge data are not available. Solution is to predict the continous discharge data are not sufficient to make that the FDC in determine the dependable flow. A method is presented to predict the daily discharge in ungauged catchments the using the method of regional Flow Duration Curve. Five gauged catchments and two ungauged catchments in the region Akuaman River, West Sumatera was chosen to develop and test the proposed method Regional FDC. Using nonlinear regression analysis, regional FDC can be developed. It than, used for flow prediction. The results indicate that FDC method shows great promise for predicting streamflow in ungauged basins. Prediction of daily discharge in the river basin Arau and Air dingin on the basis of RFDC has a high correlation is 0.9, which shows similarity to the observed discharge. Key words: flow duration curve, regional flow duration curve, ungauged basins